2001
DOI: 10.1089/15230860152542943
|View full text |Cite
|
Sign up to set email alerts
|

Metal Response Element (MRE)-Binding Transcription Factor-1 (MTF-1): Structure, Function, and Regulation

Abstract: Metal-responsive control of the expression of genes involved in metal metabolism and metal homeostasis allows an organism to tightly regulate the free or bioavailable concentration of beneficial metal ions, such as zinc, copper, and iron, within an acceptable range, while efficiently removing nonbeneficial or toxic metals. Emerging evidence also suggests that metal homeostasis is intimately coupled to the oxidative stress response in many cell types. The expression of genes that encode metallothioneins in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
115
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 73 publications
2
115
0
Order By: Relevance
“…We have recently identified and characterized dMTF-1, the MTF-1 homolog of the fruit fly Drosophila (Zhang et al, 2001;Egli et al, 2003). In both mammals and Drosophila, MTF-1 requires zinc and its function is compromised by direct exposure to other heavy metals (Bittel et al, 1998;Giedroc et al, 2001;Zhang et al, 2001). Accordingly, in a cell-free transcription system, MTF-1 activation by cadmium and copper (and H 2 O 2 ) was shown to occur indirectly, via release of zinc from metallothionein (for convenience, the designations Zn or zinc, Cu or copper, Cd or cadmium and Hg or mercury are also used here to denote Zn 2q , Cu 2q , Cd 2q and Hg 2q , respectively.)…”
Section: Introductionmentioning
confidence: 99%
“…We have recently identified and characterized dMTF-1, the MTF-1 homolog of the fruit fly Drosophila (Zhang et al, 2001;Egli et al, 2003). In both mammals and Drosophila, MTF-1 requires zinc and its function is compromised by direct exposure to other heavy metals (Bittel et al, 1998;Giedroc et al, 2001;Zhang et al, 2001). Accordingly, in a cell-free transcription system, MTF-1 activation by cadmium and copper (and H 2 O 2 ) was shown to occur indirectly, via release of zinc from metallothionein (for convenience, the designations Zn or zinc, Cu or copper, Cd or cadmium and Hg or mercury are also used here to denote Zn 2q , Cu 2q , Cd 2q and Hg 2q , respectively.)…”
Section: Introductionmentioning
confidence: 99%
“…MTF-1 contains a single DNA binding domain consisting of six zinc fingers and it is structurally and functionally conserved from Drosophila to humans (6,7). Cross-species comparison between human and Drosophila MTF-1 reveals considerable identity in the DNA binding domain (66% amino acid identity) indicating that the proteins likely interact with DNA in a conserved mode (8,9).…”
mentioning
confidence: 99%
“…Zn 2+ , in turn, can directly bind to MTF-1 and promote its nuclear translocation (Chen et al, 2004;Smirnova et al, 2000), although it has also been suggested that Zn 2+ can bind to, and inactivate a yet unidentified inhibitor of the translocation process itself (Palmiter, 1994). Nonetheless, MTF-1 translocation to the nucleus and transactivation of MRE can serve as selective molecular indicators of elevations of intracellular Zn 2+ (Giedroc et al, 2001;Smirnova et al, 2000). An important objective of this work was to demonstrate the feasibility of using a molecular reporter for the liberation of Zn 2+ from intracellular binding sites in primary neuronal cultures.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MTF-1 plays an important role in the regulation of gene expression associated with zinc home-ostasis, including metallothionein (Giedroc et al, 2001) and the zinc transporter Znt-1 (Langmade et al, 2000). In neurons, regulation of the expression of these proteins may have important consequences on neuronal survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation